2011
DOI: 10.1111/j.1525-1446.2011.00969.x
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Design and Use of an Agency Feedback Form for Student Clinical Practicum Experience in Community/Public Health Nursing

Abstract: Evaluation of students in community and public health (C/PH) nursing clinical practica is a challenge, especially when preceptors are expected to evaluate students from different academic nursing programs. The need for a standardized student evaluation tool was identified during federally funded collaborative meetings held between C/PH academic and practice partners in Northeastern Wisconsin. This article focuses on the development and appraisal of the standardized Agency Feedback Form (AFF) for Student Practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The schools have had successful prior experiences collaborating on ongoing programs (UW—Madison School of Nursing, n.d .) and on special grant‐funded projects (Reilly, et al., 2011 ; Young, et al., 2014 ; Zahner & Henriques, 2013 ), which facilitated initiating a collaboration to help with the COVID‐19 vaccination challenge. Collaboration between these five schools was also supported by the familiarity of being part of the same state university system with similar programs and infrastructure (e.g., course management systems).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The schools have had successful prior experiences collaborating on ongoing programs (UW—Madison School of Nursing, n.d .) and on special grant‐funded projects (Reilly, et al., 2011 ; Young, et al., 2014 ; Zahner & Henriques, 2013 ), which facilitated initiating a collaboration to help with the COVID‐19 vaccination challenge. Collaboration between these five schools was also supported by the familiarity of being part of the same state university system with similar programs and infrastructure (e.g., course management systems).…”
Section: Discussionmentioning
confidence: 99%
“…Many noted "once-in-a-lifetime" opportunities presented by the initiative, such as being a part of the solution, fighting COVID-19, giving back to the community, saving lives, and being a part of the response to a "historic event." special grant-funded projects (Reilly, et al, 2011;Young, et al, 2014;Zahner & Henriques, 2013), which facilitated initiating a collaboration to help with the COVID-19 vaccination challenge. Collaboration between these five schools was also supported by the familiarity of being part of the same state university system with similar programs and infrastructure (e.g., course management systems).…”
Section: Faculty Member Personal Impactsmentioning
confidence: 99%
“…In the workshop, partici- pants discussed standards of performance in relation to the common assessment tool, the VicCAT. The need for a common assessment tool has been noted as important to local contexts (Reilly et al, 2012). The postsurvey identified that the preceptorship program was effective in reducing this uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…Preceptorship in community-based primary health care services presents different challenges from preceptorship in acute health care services and therefore requires a focus on different aspects of student clinical learning. For example, focus is greater on the development of public health nursing skills and lesser on psychomotor skills (Reilly et al, 2012). Preceptors need to implement teaching and learning strategies that focus on developing the students' population health knowledge and skills that are relevant to community public health nursing practice (Callen et al, 2013).…”
Section: Preceptor Education For Specialty Community-based Nurses: a mentioning
confidence: 99%
“…In Wisconsin in the United States, Reilly et al. (2012) developed an evaluation tool based on interventions from the Wheel for preceptors to use in communication with clinical instructors about student performance. In Australia, Woods (2010) explained how Wheel interventions were used to assess students’ cognitive learning about community nursing practice interventions.…”
Section: Dissemination Of the Phi Wheelmentioning
confidence: 99%